Determination of seed physiological maturity and storability of several sorghum varieties - Karima Rizki Faizal; Satriyas Ilyas; Abdul Qadir; Soeranto Human (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2025)
Seed vigor reaches a maximum at physiological maturity and decreases during storage. This study aimed to determine the physiological maturity and enhance the storability of sorghum seeds. Experiments were conducted at BRIN Lebak-Bulus from March 2023 to March 2024. The initial experiment employed a two-factor randomized complete block design, incorporating five sorghum varieties and five seed maturity levels. The second experiment used a complete randomized design with two factors (nest: temperature storage 18 °C and 26 °C, and nested: combined seed moisture content (MC) 10-11% and 12-13%, and storage period (1-24 weeks). The results indicated the seed physiological maturity stages of the five sorghum varieties were: Numbu 46 days after anthesis (DAA), Super-1 39 DAA, Bioguma-1 51 DAA, Samurai-2 55 DAA, and Pahat 40 DAA. The Numbu stored at 18 °C, 10-11% MC had storability up to 24 weeks (72.3% germination) and at 18 °C, 12-13% MC up to 20 weeks (72.3%), while at 26 °C, 10-11% MC had storability up to 18 weeks (71.3%) and 26 °C, 12-13% MC up to 22 weeks (70.3%). The Bioguma-1 and Samurai-2 seeds were suspected of having after-ripening dormancy. From the beginning until 24 weeks, they did not deteriorate, although the viability was below 70%. Keywords: germination; seed moisture content; storage period; viability; vigor